2022
DOI: 10.3346/jkms.2022.37.e124
|View full text |Cite
|
Sign up to set email alerts
|

Short Term Impact of Coronavirus Disease 2019 Vaccination in Children in Korea

Abstract: Background The epidemiology of coronavirus disease 2019 (COVID-19) has changed continuously throughout the pandemic. Methods We analyzed changes in the incidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection according to the age group in South Korea from February 2020 to December 2021. Results Since the COVID-19 pandemic, the incidence among adults aged ≥ 18 years was higher than all the other age groups in 2020; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In South Korea, the increase of SARS‐CoV‐2 cases during the first half of 2022 was largely driven by children and adolescents with limited vaccine coverage, suggesting a possible role of vaccine‐induced immunity in preventing SARS‐CoV‐2 reinfections. 10 Higher rates of reinfection among children (470 per 100 000, compared to 240–280 per 100 000 in adults) and unvaccinated persons (530–640 per 100 000, compared to 210‐400 per 100 000 in fully vaccinated persons) support such hypothesis. This higher vaccination coverage could lead to a lesser chance of reinfections in the community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In South Korea, the increase of SARS‐CoV‐2 cases during the first half of 2022 was largely driven by children and adolescents with limited vaccine coverage, suggesting a possible role of vaccine‐induced immunity in preventing SARS‐CoV‐2 reinfections. 10 Higher rates of reinfection among children (470 per 100 000, compared to 240–280 per 100 000 in adults) and unvaccinated persons (530–640 per 100 000, compared to 210‐400 per 100 000 in fully vaccinated persons) support such hypothesis. This higher vaccination coverage could lead to a lesser chance of reinfections in the community.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may reflect the difference in risk of exposure between the population, such as young adults and healthcare professionals, with a persistently higher risk of exposure compared to the general population. In South Korea, the increase of SARS‐CoV‐2 cases during the first half of 2022 was largely driven by children and adolescents with limited vaccine coverage, suggesting a possible role of vaccine‐induced immunity in preventing SARS‐CoV‐2 reinfections 10 . Higher rates of reinfection among children (470 per 100 000, compared to 240–280 per 100 000 in adults) and unvaccinated persons (530–640 per 100 000, compared to 210‐400 per 100 000 in fully vaccinated persons) support such hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in mortality of ages 5 to 19 during the year 2021 coincides with rapid increase in COVID-19 patients of that particular age group [ 53 ]. Although COVID-19 vaccination for adults started in February 2021, the vaccination for adolescents (12 to 17 years) was delayed until October 2021 in Korea [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although COVID-19 vaccination for adults started in February 2021, the vaccination for adolescents (12 to 17 years) was delayed until October 2021 in Korea [ 54 ]. Until the adoption of vaccination, 12 to 17 years age group showed highest incidence since the second quarter of 2021 [ 53 ], and this may have resulted in higher excess mortality of that age group during year 2021. Age-specific mortality patterns of the younger age group in our study also showed an increase in COVID-19 mortality since July 2021 (Figure S 3 ).…”
Section: Discussionmentioning
confidence: 99%
“… 14 COVID-19 vaccination started in adolescents since October 2021, reaching vaccine coverage of 67.8% for one dose and 46.3% for two doses, by the end of 2021. 15 COVID-19 vaccination in children aged 5–11 started since March 2022, with low coverage of 1% by August 2022. 16 …”
Section: Methodsmentioning
confidence: 99%